Treating postmenopausal osteoporosis in women at increased risk of fracture – critical appraisal of bazedoxifene: a review - Peter Vestergaard; Susanna vid Streym Thomsen (Dove Medical Press, 2009)
Peter Vestergaard, Susanna vid Streym ThomsenDepartment of Endocrinology and Metabolism C, Aarhus University Hospital, Aarhus, DenmarkAbstract: Several categories of drugs to treat osteoporosis exist in the form of bisphosphonates, strontium, parathyroid hormone, and selective estrogen receptor modulators (SERM). Advantages and disadvantages exist for each category as some patients may, for example, not tolerate bisphosphonates for gastrointestinal side effects, and especially in women in whom osteoporosis is frequent, several options for treatment are needed. The objectives of this review were to critically appraise the effects of bazedoxifene on risk of fractures especially in women at high risk of fractures. A systematic literature search was conducted for studies, especially randomized controlled trials with fractures as end-points. Bazedoxifene is a new member of the SERM group. The literature search identified one randomized controlled trial with fractures as end-point. This was a 3-year randomized double-blind placebo controlled trial in which 7492 postmenopausal women aged 55 to 85 years were randomly allocated to 1) bazedoxifene (20 [n = 1886] or 40 [n = 1872] mg/day); 2) raloxifene (60 mg/day, n = 1849); or 3) placebo (n = 1885). The risk of vertebral fractures decreased with both 20 (HR 0.58, 95% CI 0.38 to 0.89) and 40 (HR 0.63, 95% CI 0.42 to 0.96) mg of bazedoxifene per day compared to placebo. There was no reduction in non-vertebral fractures. A subgroup of women with a priori high risk of fractures was identified post hoc. In this subgroup there was a reduction in the risk of non-vertebral fractures with the 20 mg dose of bazedoxifene compared to placebo (HR 0.50, 95% CI 0.28 to 0.90). In the 40 mg bazedoxifene group no significant reduction in non-vertebral fractures was seen in this subgroup (HR 0.70, 95% CI 0.40 to 1.20). In general post-hoc defined subgroup analyses should be interpreted with caution. However, the results indicate that bazedoxifene may be effective in preventing vertebral fractures in postmenopausal women with osteoporosis.Keywords: bazedoxifene, fracture, bone mineral density